Evaluating others’ well-being: Survey experiment on fictional Japanese celebrities generated from wikipedia articles and ChatGPT - Takaharu Saito; Aguru Ishibashi; Zeyu Lyu; Zhemeng Xie; Sachiko Yasuda; Hiroki Takikawa (PLoS ONE, 2026)
Well-being attracts scholars’ and policymakers’ interests for decades. This study examines how respondents evaluate a “Good Life,” “Happy Life,” and “Meaningful Life” through the analysis of fictional celebrity articles using the supervised Indian Buffet Process (sIBP). We identify key patterns in well-being perception, highlighting the importance of artistic engagement, public influence, and career success across all three dimensions. While happiness is closely linked to career achievements and personal stability, meaning is driven by cultural and artistic contributions, and a good life balances both elements. Personal hardships negatively impact all three dimensions but are particularly detrimental to happiness. Conversely, creative contributions and public engagement enhance perceptions of a meaningful life. These findings suggest that external success and intrinsic fulfillment are both essential for well-being. Our approach demonstrates the value of computational text analysis in uncovering nuanced insights into societal conceptions of a fulfilling life, paving the way for further interdisciplinary research on well-being and perception.